Biological, ecological and trophic features of invasive mosquitoes and other hematophagous arthropods: What makes them successful? - David Renault; Stéphane A. P. Derocles; Phillip Haubrock; Frédéric Simard; Ross N. Cuthbert; Claire Valiente-Moro (Biological Invasions, 2024)

Regulating cancer risk prediction: legal considerations and stakeholder perspectives on the Canadian context - Palmira Granados Moreno; Terese Knoppers; Ma’n H. Zawati; Michael Lang; Bartha M. Knoppers; Michael Wolfson; Hermann Nabi; Michel Dorval; Jacques Simard; Yann Joly (Human Genetics, 2023)
Risk prediction models hold great promise to reduce the impact of cancer in society through advanced warning of risk and improved preventative modalities. These models are evolving and becoming more complex, increasingly integrating genetic screening data and polygenic risk scores as well as calculating risk for multiple types of a disease. However, unclear regulatory compliance requirements applicable to these models raise significant legal uncertainty and new questions about the regulation of medical devices. This paper aims to address these novel regulatory questions by presenting an initial assessment of the legal status likely applicable to risk prediction models in Canada, using the CanRisk tool for breast and ovarian cancer as an exemplar. Legal analysis is supplemented with qualitative perspectives from expert stakeholders regarding the accessibility and compliance challenges of the Canadian regulatory framework. While the paper focuses on the Canadian context, it also refers to European and U.S. regulations in this domain to contrast them. Legal analysis and stakeholder perspectives highlight the need to clarify and update the Canadian regulatory framework for Software as a Medical Device as it applies to risk prediction models. Findings demonstrate how normative guidance perceived as convoluted, contradictory or overly burdensome can discourage innovation, compliance, and ultimately, implementation. This contribution aims to initiate discussion about a more optimal legal framework for risk prediction models as they continue to evolve and are increasingly integrated into landscape for public health.

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Selected cancers with increasing mortality rates by educational attainment in 26 states in the United States, 1993–2007 - Ahmedin Jemal; Edgar P. Simard; Jiaquan Xu; Jiemin Ma; Robert N. Anderson (Cancer Causes & Control, 2013)

What explains landscape patterns of tree mortality caused by bark beetle outbreaks in Greater Yellowstone? - Martin Simard; Erinn N. Powell; Kenneth F. Raffa; Monica G. Turner (Global Ecology and Biogeography, 2012)
Aim Bark beetle outbreaks have recently affected extensive areas of western North American forests, and factors explaining landscape patterns of tree mortality are poorly understood. The objective of this study was to determine the relative importance of stand structure, topography, soil characteristics, landscape context (the characteristics of the landscape surrounding the focal stand) and beetle pressure (the abundance of local beetle population eruptions around the focal stand a few years before the outbreak) to explain landscape patterns of tree mortality during outbreaks of three species: the mountain pine beetle, which attacks lodgepole pine and whitebark pine; the spruce beetle, which feeds on Engelmann spruce; and the Douglas‐fir beetle, which attacks Douglas‐fir. A second objective was to identify common variables that explain tree mortality among beetle–tree host pairings during outbreaks. Location Greater Yellowstone ecosystem, Wyoming, USA. Methods We used field surveys to quantify stand structure, soil characteristics and topography at the plot level in susceptible stands of each forest type showing different severities of infestation (0–98% mortality; n = 129 plots). We then used forest cover and beetle infestation maps derived from remote sensing to develop landscape context and beetle pressure metrics at different spatial scales. Plot‐level and landscape‐level variables were used to explain outbreak severity. Results Engelmann spruce and Douglas‐fir mortality were best predicted using landscape‐level variables alone. Lodgepole pine mortality was best predicted by both landscape‐level and plot‐level variables. Whitebark pine mortality was best – although poorly – predicted by plot‐level variables. Models including landscape context and beetle pressure were much better at predicting outbreak severity than models that only included plot‐level measures, except for whitebark pine. Main conclusions Landscape‐level variables, particularly beetle pressure, were the most consistent predictors of subsequent outbreak severity within susceptible stands of all four host species. These results may help forest managers identify vulnerable locations during ongoing outbreaks.

Cognitive-impairing effects of medroxyprogesterone acetate in the rat: independent and interactive effects across time - B. Blair Braden; Alexandra N. Garcia; Sarah E. Mennenga; Laszlo Prokai; Stephanie R. Villa; Jazmin I. Acosta; Natalie Lefort; Alain R. Simard; Heather A. Bimonte-Nelson (Psychopharmacology, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

Role of the UL28 homologue of bovine herpesvirus 1 in viral DNA cleavage and packaging - N. Desloges; C. Simard (Archives of Virology, 2003)

Expression kinetics of the late UL12 gene encoding the bovine herpesvirus 1 alkaline nuclease - N. Desloges; C. Simard (Archives of Virology, 2001)

Transcriptional and translational expression kinetics of the UL25 homologue of bovine herpesvirus 1.1 - N. Desloges; H. Boucher; C. Simard (Archives of Virology, 2001)

SMN gene duplication and the emergence of the SMN2 gene occurred in distinct hominids: SMN2 is unique to Homo sapiens - C. Rochette; N. Gilbert; L. Simard (Human Genetics, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)